Occult Hepatitis B infection (OBI) in vaccinated groups, a metanalysis - Alavian, Seyed Moayed; Jazayeri, Seyed Mohammad (Archives of Medical Laboratory Sciences, 2019)
Nowadays, the presence of HBV DNA in the absence of HBsAg; occult hepatitis B infection; (OBI), is a known clinical entity along with the rapid influx of research being conducted on its clinical relevance. Biologists and clinicians alike have a recent-standing interest in this regards. OBI has been described in several clinical settings. However, the data on its prevalence among immunized and non-immunized healthy general population, in particular, among health care workers (HCWs) is ambigous. This review attemps to explore the significance of OBI in vaccinated groups as a special subject. The prevalence of OBI among general population, vaccinated children/general population and health care workers were: 157 (5.2%), 222 (6.7%) and 33 (1.8%), respectively. The prevalence of anti-HBc among OBI-positive subjects were: 64 (40.7%), 133 (82.7%) and 27 (81.8%), respectively. OBI is partly prevalent in general population and in vaccinated individuals, especially in those who born to HBsAg positive mothers. HBV serological surveys are not enough adequate and sensitive to rule out the presence of HBV DNA. For high-risk groups (subjects born to HBsAg mothers, health care workers, isolated anti-HBc, etc) sensitive molecular tests based on real time PCR should be applied for a proper diagnosis.